Segmented regression analysis of emergency departments patient visits from Septicemia in Taiwan. Issue 2 (June 2018) - Tzeng, I-Shiang; Chien, Kuo-Liong; Tu, Yu-Kang; Chen, Jau-Yuan; Ng, Chau Yee; Chien, Cheng-Yu; Chen, Jih-Chang; Chaou, Chung-Hsien; Yiang, Giou-Teng
Abstract: Background: The protocol for early goal-directed therapy (EGDT) is effective for improving both the costs and outcomes of septicemia treatment, including a significant reduction in case fatality. However, this complicated protocol may have a downside. Furthermore, the Joint Taiwan Critical Care Medicine Committee has launched a nationwide educational program after the publication of the Surviving Sepsis Campaign (SSC) to improve the overall survival rate from septicemia in the emergency care system of Taiwan. Objectives: To assess the impact of the EGDT protocol and SSC education programs on island-wide septicemia-related emergency department (ED) visits. Methods: Segmented regression techniques were utilized to assess the differences in annual rates and changes in septicemia-related ED visits between 1998 and 2012. We considered annual incidence of two medical comorbidities as potential confounders: metastatic malignant neoplasms and malignant neoplasms of the lymphatic and hematopoietic tissues. Results: The EGDT protocol was associated with decreased septicemia-related ED visits in 2002 (level change; p < 0.001), while the SSC education program led to a slight increase in septicemia-related ED visits in 2007 (slope change; p < 0.001). For the EGDT protocol, the number of patient visits decreased by 32.9% after the protocol was implemented in 2002 compared with the expected number without the intervention. For the SSC education program, the number of patient visits increased by 20.2% (compared with the predicted number) in 2007 after the education program was implemented. Conclusions: The EGDT protocol and SSC education program were associated with significant immediate changes and lagged intervention effects on island-wide septicemia-related ED visits. Highlights: The early goal-directed therapy (EGDT) and the Surviving Sepsis Campaign (SSC) program may increase awareness of the diagnosis of septicemia-related visits in emergency departments (ED). Previous studies have demonstrated the implementation of the EGDT and SSC program in developed countries is associated with improved patient outcomes. However, the impact of the EDGT and SSC program on ED septicemia-related visits was unclear. The EGDT and SSC program were associated with significant immediate changes and lagged intervention effects on island-wide septicemia-related ED visits.